THE USE OF MOTHER TONGUE FOR EDUCATION FIELD IN MULTILINGUAL SOCIETY, BALI-INDONESIA - Md. Yudyantara Risadi; I Ketut Ardiasa (Denpasar Institute, 2020)
This study aimed to find out the role of mother tongue language as the instruction in multilingual society and the importance of mother tongue language as the instruction in multilingual society, such as Bali. The data was collected through library research to find out the role of mother tongue in multilingual society and conducting interview in rural area and urban area to find out how importance of mother if it is used as the instruction in the classroom. The result showed that there are 5 role of mother tongue in multilingual society and there is a contrast opinion of the importance of mother tongue as the instruction in rural and urban area.